The accuracy of digital scanners versus conventional impression in patients with cleft lip and palate: A cross-sectional study - Natthasit Pudpong; Subin Puasiri; Amornrut Manosudprasit (Saudi Dental Journal)
Background and Objectives: As the use of digital models has expanded across numerous fields, the accuracy of three-dimensional images captured by various intraoral scanners has become a key research focus. This study aimed to evaluate the accuracy of digital scanners (TRIOS 4, iTero Element 5D, and E2) compared with the conventional impression method (gold standard) in patients with cleft lip and palate. Materials and Methods: Impressions were taken from 20 patients using these scanners and alginate impressions during the same session. Additionally, plaster models were created and scanned using an E2 scanner, and 50 parameters were measured using a digital caliper. All digital models were then analyzed using 3Shape software. Measurement reliability and differences among the four methods were assessed by repeated measures analysis of variance (ANOVA), followed by post-hoc analysis. Subsequently, best-fit superimposition was performed to verify the deviated areas between the digital models. Results: The plaster cast measurements and digital models obtained using three different scanners revealed high reliability (0.94–1.00). Statistically significant differences between the dental models were observed in 20 out of 50 parameters (p < 0.05). Mean differences in hard tissue parameters between groups ranged from −0.47 to 0.32 mm. Soft tissue parameters revealed more considerable mean differences, ranging from −1.59 to 2.55 mm. The measured palatal depth obtained from digital models was significantly higher, while the depth of the oronasal fistula was significantly lower compared to plaster models. Conclusion: This study concluded that digital scanners have accuracy comparable to conventional methods, except for depth-related soft tissue parameters, which exhibited a high level of discrepancy.